2012
DOI: 10.2174/187152812800959040
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21 in Immune and Allergic Diseases

Abstract: Interleukin-21 (IL-21), a cytokine produced by various subsets of activated CD4+ T cells, plays a major role in the control of innate and adaptive immune responses. IL-21 biological activity is mediated by binding of the cytokine to a heterodimeric receptor, composed of a specific subunit, termed IL-21 receptor (IL-21R), and the common γ-chain, that is shared with IL-2, IL-4, IL-7, IL-9 and IL-15 receptors. IL-21 stimulates the proliferation of CD4+ and CD8+ T lymphocytes and regulates the profile of cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 72 publications
(117 reference statements)
2
19
0
Order By: Relevance
“…These data are consistent with recent studies from the laboratories of Leonard and Sarvetnick [32], showing that IL-21R –/– NOD mice are protected from insulitis and type 1 diabetes. Interleukin-21 could also play a role in the pathogenesis of other immune-mediated pathologies as its levels were found to be up-regulated in synovial tissue samples of patients with rheumatoid arthritis (RA) and in labial salivary gland sections of patients with Sjögren's syndrome (SS), as well as in the plasma of patients with SS, patients with Behçet disease, and patients with Hashimoto's thyroiditis [33]. A previous published study showed that IL-21 was not able to trigger Th1 cell differentiation, but it could enhance ongoing Th1 cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with recent studies from the laboratories of Leonard and Sarvetnick [32], showing that IL-21R –/– NOD mice are protected from insulitis and type 1 diabetes. Interleukin-21 could also play a role in the pathogenesis of other immune-mediated pathologies as its levels were found to be up-regulated in synovial tissue samples of patients with rheumatoid arthritis (RA) and in labial salivary gland sections of patients with Sjögren's syndrome (SS), as well as in the plasma of patients with SS, patients with Behçet disease, and patients with Hashimoto's thyroiditis [33]. A previous published study showed that IL-21 was not able to trigger Th1 cell differentiation, but it could enhance ongoing Th1 cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…The effects are mediated by the heterodimeric receptor complex IL-21 R and the common g chain shared by cytokines in the IL-2 superfamily (Sarra et al, 2012). Since IL-21 Rs are widely distributed, IL-21 has pleiotropic effects which have only been recently explored in bone.…”
Section: Interleukin-21mentioning
confidence: 99%
“…The biological functions of IL-21 are mediated by a heterodimeric receptor, formed by a common γ-chain subunit, which is shared with the IL-2, IL-4, IL-7, IL-9 and IL-15 receptors, and its own unique receptor (designated IL-21R), a member of the class I cytokine receptor family ( Fig. 1) (7,8). Although IL-21 production is restricted to lymphoid populations, IL-21R is highly expressed on a range of immune (i.e., naïve and activated T cells, B cells, NK cells, dendritic cells and macrophages), as well as non-immune cells (i.e., keratinocytes and endothelial cells) (7,8), indicating a broad spectrum of functions.…”
Section: Il-21 and Il-21 Receptor Expression And Signalingmentioning
confidence: 99%
“…1) (7,8). Although IL-21 production is restricted to lymphoid populations, IL-21R is highly expressed on a range of immune (i.e., naïve and activated T cells, B cells, NK cells, dendritic cells and macrophages), as well as non-immune cells (i.e., keratinocytes and endothelial cells) (7,8), indicating a broad spectrum of functions. Of note, the expression of IL-21R on B cells was the highest, even on resting cells (1).…”
Section: Il-21 and Il-21 Receptor Expression And Signalingmentioning
confidence: 99%